Monitoring of Polycyclic Aromatic Hydrocarbons (PAHs) in Scottish Deepwater environments. (March 2018) - Webster, L.; Russell, M.; Shepherd, N.; Packer, G.; Dalgarno, E.J.; Neat, F.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) were measured in environmental samples (sponges, fish and sediment) collected in 2014 and 2016 from the Faroe-Shetland Channel and Rosemary Bank Seamount. These data could be used to provide a baseline against which any changes can be assessed in the event of an oil spill and contribute to any environmental impact assessment. Concentrations in all samples were low, often below the detection limits, and were typical of reference sites. Sponges can be used as an alternative indicator species to mussels for monitoring PAHs in the marine environment as they can accumulate PAHs from both the dissolved and particulate phase. PAH concentrations in marine sponges from Scottish waters have not previously been reported. Concentrations were low, but contained a higher proportion of heavier 4- to 6-ring PAHs compared to the fish samples. Graphical abstract: Unlabelled Image Highlights: Baseline PAH data was obtained for Scottish deepwater environments. PAH concentrations in fish and sediment were low and typical of reference sites. A higher proportion of 4- to 6-ring PAHs were found in the sponges compared to fish. Sponges may be useful as an indicator species for monitoring PAHs.